Customer's satisfaction towards Customer Service Centre of Syarikat Air Melaka Berhad, Bangunan Graha Maju, Melaka / Mohammad Sufian Abdul Manan - Abdul Manan, Mohammad Sufian (Faculty of Business and Management, 2008)
The purpose of this research is to measure the customer satisfaction towards Customer Service Centre that was under supervision of Syarikat Air Melaka Berhad. The main objectives of this research are, to determine significant relationship between customer satisfaction and responsiveness, reliability and knowledge, to determine factor that contributes most to customer satisfaction and to determine the level of satisfaction of customers towards Customer Service Centre of Syarikat Air Melaka Berhad. This study use primary data as the main method of data collection. The survey was undertaken both in English and Bahasa Melayu language. One hundred questionnaires are distributed and were return back. Here, customer satisfaction was assessed through statements relating to the responsiveness, reliability and knowledge. For data analysis, the researcher will use SPSS (Statistical Package For Social Science). The researcher will use Cronbach's Alpha to measure the reliability of the questionnaire, cross tabulation for hypotheses testing in examining relationship among variables, and frequency table to look for satisfaction. From the findings, it can be concluded that most of the respondents are satisfied with the service provided by Customer Service Centre of Syarikat Air Melaka Berhad. Based on the hypotheses testing, the results indicate that there is significant relationship between responsiveness, reliability and knowledge towards customer satisfaction. The result is supported by Festus Olorunniwo, et. al (2006) for responsiveness and knowledge and by Arawati Agus, et. al, (2007) for reliability.